A Class of Relational Functional Contractions with Applications to Nonlinear Integral Equations - Khursheed J. Ansari; Salvatore Sessa; Aftab Alam (Mathematics, 2023)
In this article, we investigate some fixed-point results under certain functional contractive mappings in a relation metric space. In the process, we utilize more general contraction condition which must be verified for comparative elements only. Our results enrich, modify, refine, unify and sharpen several existing fixed-point results. We construct some examples in support of our results. To attest to the applicability of our results, we establish the existence and uniqueness of theorems regarding the solutions of certain nonlinear integral equations.